Why Do Accounting and Business Lecturers Accept Digital Game-Based Learning? - Tan Ming Kuang; Hanny Hanny; Santy Setiawan (Jurnal ASET (Akuntansi Riset), 2022)
Digital game-based learning has a potential to help accounting and business students acquiring knowledge and skills required for industry 4.0.  However, its adoption and effectiveness rely heavily on lecturer acceptance because they are the real agent of change in Higher Education Institution. In this study, a modified TAM model to examine and predict lecturer acceptance of digital game-based learning is proposed, and empirically tested by involving 258 acounting and business lecturers. The results show that lecturers’ intention for adopting digital game-based learning in the classroom is affected directly by several factors: usefulness, subjective norm, and personal innovativeness. Although curriculum effects are not found, its effects appear to be mediated by usefulness. This study does not find direct and indirect impact of critical mass on lectures’ intention for adopting digital game-based learning.